Value Chain Analysis on Handmade Batik Products - Sari, Suzanna Ratih; Arifan, Fahmi; Triyono, Triyono; Niswah, Ulfatun (Universitas Negeri Semarang, 2020)
Since the recognition of batik by UNESCO, the batik market has expanded throughout the world. This is marked by the increase in the value of batik exports to various countries. In the midst of increasingly fierce trade competition, industries are demanded to be capable and have high competitiveness. Although batik is considered as one of the strategic industries, in terms of development, batik still faces several problems both internally and externally. The purpose of this research is to discuss about the solution to develop batik in Cibelok Village, Pemalang Regency by analyzing the value chain so that it increases the selling value of written batik. This study used a value chain analysis approach, Competitiveness Diamond, and Critical Success Factor Value. Based on the results of the analysis, it was found that the profit generated per onefabric production is Rp74,700. Increasing profit margins can be done by considering the role of several activities in the batik business process. The activities to consider are operations, followed by marketing and sales, as well as inbound logistics. In addition, product quality and innovation in batik patterns are needed in an effort to increase sales.